Arendt, Koselleck, and Begreifen: Rethinking Politics and Concepts in Times of Crisis - Jalušič, Vlasta (Filozofski vestnik, 2024)
Reinhard Koselleck has long been regarded as a particularly eminent theorist of socio-political concepts, while Hannah Arendt had not been in focus as a conceptual author until recent times. This article explores the common thinking space between Arendt and Koselleck through their thesis about the gap, rupture, crisis, or break in the tradition of political thinking and historical periods and how this is linked to their notion of conceptuality, i.e. Begreifen (understanding). Despite the impression that each of them focused on the one main break between the past and the future, Arendt and Koselleck both studied multiple breaks and crises in the Western political tradition. The article attempts to show how their distinctive thinking and rethinking of political concepts (Begreifen) are related to these breaks through several direct and indirect encounters and how these are both close and apart at the same time. While they have different concepts of politics and the political, their understanding of the breaks in time and crises can be read as complementary, especially considering their concern with returning the responsibility for actions and concepts to the human sphere.